Anticancer Prospects of Earthworm Extracts: A Systematic Review of In vitro and In vivo Studies - Augustine, Dominic; Rao, Roopa S.; Anbu, Jayaraman; Murthy, K. N. Chidambara (Pharmacognosy Reviews)
In recent times, naturally occurring substances such as earthworm extracts have been used successfully as an antimicrobial and anti‑inflammatory agent in wound healing. It has also shown promising antitumor activity in cervical and gastric cancer. The aim of this systematic review is to analyze the anticancer potentials of earthworm extracts. Several databases, including PubMed and Google Scholar, were searched from September 2001 to September 2017 using combinations of the following keywords “Earthworm,” “earthworm extract,” and “anti‑cancer effect.” Original studies in English describing cytotoxic effects of earthworm extracts on cancer cells in vitro and in vivo were included in the study. We excluded letters to the editor, reviews, and unpublished data, antimicrobial and anti‑inflammatory studies pertaining to the extracts. There were 23 studies included in the analysis. Eighteen were in vitro studies and 4 studies combined in vitro and in vivo methods. Only one exclusive in vivo study was identified. Eisenia foetida was the most commonly researched earthworm species. Cervical cancer and hepatocellular carcinoma were the most commonly evaluated cancer types. HeLa cervical cancer cell line was the most commonly used model for cytotoxicity testing. Earthworm extracts showed satisfactory anticancer effect on several types of cancers, especially cervical cancer and hepatocellular carcinoma. The mechanism of apoptosis of cancer cells should be ascertained and the underlying genes and pathways responsible to be determined. This would help to execute long‑term randomized controlled trials to assess the clinical efficacy, optimum dosage, and safety in the future.
Keywords: Anticancer effect; cancer cell biology; cervical cancer; earthworm extract; Eisenia Foetida; Eudrilus eugeniae; hepatocellular carcinoma; in vitro; in vivo; proliferation